Fusarithioamide B, a new benzamide derivative from the endophytic fungus Fusarium chlamydosporium with potent cytotoxic and antimicrobial activities. Issue 3 (1st February 2018) - Ibrahim, Sabrin R.M.; Mohamed, Gamal A.; Al Haidari, Rwaida A.; Zayed, Mohamed F.; El-Kholy, Amal A.; Elkhayat, Ehab S.; Ross, Samir A.
Graphical abstract: Highlights: The EtOAc extract of Fusarium chlamydosporium isolated from Anvillea garcinii leaves was investigated. One new and 5 known compounds were isolated. Their structures were established by various spectroscopic analyses. The antimicrobial and cytotoxic capacities of the new compound were evaluated. Abstract: Fusarithioamide B (6 ), a new aminobenzamide derivative with unprecedented carbon skeleton and five known metabolites: stigmast-4-ene-3-one (1 ), stigmasta-4, 6, 8(14), 22-tetraen-3-one (2 ), p -hydroxyacetophenone (3 ), tyrosol (4 ), and fusarithioamide A (5 ) were separated from Fusarium chlamydosporium EtOAc extract isolated from Anvillea garcinii (Burm.f.) DC. leaves (Asteraceae). The structure elucidation and complete assignment of the isolated metabolites were performed mainly by the aid of various NMR and MS data. Fusarithioamide B (6 ) has been assessed for antibacterial and antifungal activities towards various microbial strains by disc diffusion assay. It exhibited selective antifungal activity towards C. albicans (MIC 1.9 µg/ml and IZD 14.5 mm), comparing to clotrimazole (MIC 2.8 µg/ml and IZD 17.9 mm). Also, it possessed high antibacterial potential towards E . coli, B. cereus, and S . aureus compared to ciprofloxacin. Furthermore, 6 was tested for the in vitro cytotoxic effect against KB, HCT-116, BT-549, MCF-7, SKOV-3, and SK-MEL cell lines. It had selective and potent effect towards BT-549, MCF-7, SKOV-3, and HCT-116 cell lines with IC50 s 0.09, 0.21, 1.23, and 0.59 μM, respectively compared to doxorubicin (IC50 s 0.046, 0.05, 0.321, and 0.24 μM, respectively). Fusarithioamide B may provide a lead molecule for future developing of antitumor and antimicrobial agents.